divide both sides of equation by 9
x-5=4x-5
or
4x-5=x-5
add 5 and -x on both sides
4x-5-x+5=x-5-x+5
3x=0
divide both sides by 3
3x/3=0/3
x=0
9(x-5)=4x-5
solve for x.
please help me with this one and show the work so i can understand
3 answers
The instructions were correct, but the execution went awry:
divide both sides by 9
x-5 = (4x-5)/9 = 4x/9 - 5/9
add 5 - 4x/9 to both sides
x - 4x/9 = 5 - 5/9
5x/9 = 40/9
x = 8
final step -- check your answer:
x=0 does not work.
9(8-5) = 27 = 32-5
divide both sides by 9
x-5 = (4x-5)/9 = 4x/9 - 5/9
add 5 - 4x/9 to both sides
x - 4x/9 = 5 - 5/9
5x/9 = 40/9
x = 8
final step -- check your answer:
x=0 does not work.
9(8-5) = 27 = 32-5
if i may say it would probably be easier and less complicated if you had follow PEMDAS instruction which tells you to take the equation on the left 9(x-5) and multiply it out first instead of dividing the two equation by 9. that way you get 9x-45=4x-5, subtract 4x from both side so you get 5x-45=-5 and then add 45 to both side to get 9x=40 and then divide by 9 so that you get x on it own to get 40/9 and you messed up the math a little near the endx-4x/9 wouldnt have given you 5x/9